2000
DOI: 10.1093/emboj/19.23.6341
|View full text |Cite
|
Sign up to set email alerts
|

The MEK1-ERK1/2 signaling pathway promotes compensated cardiac hypertrophy in transgenic mice

Abstract: Members of the mitogen-activated protein kinase (MAPK) cascade such as extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK) and p38 are implicated as important regulators of cardiomyocyte hypertrophic growth in culture. However, the role that individual MAPK pathways play in vivo has not been extensively evaluated. Here we generated nine transgenic mouse lines with cardiac-restricted expression of an activated MEK1 cDNA in the heart. MEK1 transgenic mice demonstrated concentric hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
516
3
20

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 722 publications
(581 citation statements)
references
References 55 publications
34
516
3
20
Order By: Relevance
“…The ERK-1/2 signaling was shown to promote adaptive hypertrophy with normalized wall stress and compensation for increased load. 30,31 Our study documented that R-568 increased ERK-1/2 activation. As the LVH was unaltered, one might argue that the treatment did not prevent the cardiac hypertrophy but shifted the signaling toward adaptive growth instead of fibrosis.…”
Section: Discussionmentioning
confidence: 53%
“…The ERK-1/2 signaling was shown to promote adaptive hypertrophy with normalized wall stress and compensation for increased load. 30,31 Our study documented that R-568 increased ERK-1/2 activation. As the LVH was unaltered, one might argue that the treatment did not prevent the cardiac hypertrophy but shifted the signaling toward adaptive growth instead of fibrosis.…”
Section: Discussionmentioning
confidence: 53%
“…In this study, we found that ERK1/2 phosphorylation significantly decreased but p38MAPK phosphorylation increased in Gab1-cKO mice compared with Gab1-WT mice under pressure overload. ERK1/2 phosphorylation is associated with concentric LV hypertrophy without signs of progression toward heart failure, 54 and is thought to be a component of an consequential adaptive mechanism in the myocardium. 55 The blunting of the ERK1/2 signaling using a dominant-negative Raf1 blocks adaptive cardiac hypertrophy, accompanied by an increase in apoptosis, and LV dysfunction, concluding with an enhancement in mortality rate when subjected to pressure overload.…”
Section: Resultsmentioning
confidence: 99%
“…Mitogen‐activated protein kinases (MAPKs) and, especially, extracellular signal‐regulated kinase (ERK), which is activated by virtually all hypertrophic stimuli in cardiomyocytes, represent the central pathway regulating transcription of ANP and BNP 17. Constitutive activation of MEK1 (upstream activator of ERK) in myocytes induces cardiac hypertrophy and NP expression,18 but loss of ERK from cardiomyocytes is not sufficient to block stress‐induced hypertrophic response 19. In addition to ERK, p38 MAPK has been shown to regulate NP expression in primary cardiomyocyte culture.…”
Section: Regulation Of Anp and Bnp Gene Expressionmentioning
confidence: 99%